Interior designer's portable handbook first-step rules of thumb for the design of interiors - Guthrie, Pat (New York McGraw-Hill, 2012)
Fully revised throughout, Interior Designer's Portable Handbook, Third Edition, helps you create workable, on-the-spot design solutions by putting the latest codes, standards, specifications, costs, and materials data at your fingertips. This convenient pocket guide now includes information on green/sustainable components and technologies. Perfect for in-the-field estimating as well as licensing exam prep, this indispensable, time-saving tool helps you with everyday design challenges.
Includes bibliographical references and index.
Keywords: Interior decoration -- Handbooks, manuals, etc; Architectural design -- Handbooks, manuals, etc